Bottom-up characterization of the residential - Artur, Bauer; Soheil, Lazemi-Wanjani (My University, 2012)
In many countries of the European Union, the largest potential for energy efficiency improvements lies in retrofitting houses, since the energy consumption of residential and non-residential buildings in the European Union had the largest share with 39 % in 2009. Currently, there is a lack of information about the building stock and associated modelling tools, which can be used to assess such measurements as basis for energy efficiency strategies and policy design to be applied to the European building sector. Therefore, a methodology has been developed that represents the European building stock as reference buildings with the aim to assess the effects of energy saving measures. The model used for the building energy simulation is the Energy Assessment for Buildings Stocks (EABS). By applying the EABS model, the final energy and heating demand for the German residential stock could be calculated and provided a base for further investigation considering the assessment for retrofitting residential houses in Germany.
Keywords: Energi; Hållbar utveckling; Mekanisk energiteknik; Termisk energiteknik; Energy; Sustainable Development; Mechanical energy engineering; Thermal energy engineering